Polycaprolactone microcapsules containing citric acid and naringin for plant growth and sustainable agriculture: physico-chemical properties and release behavior - Cesari, Adriana Belen (2020)
Plant growth promoting rhizobacteria (PGPR) is an alternative to chemical fertilizers for sustainable, environment friendly agriculture. There is a need to develop strategies to potentiate the interaction between rhizobacteria and plants. Flavonoids and organic acids (components of root exudates) play specific beneficial roles as carbon sources and signal molecules in the plant – rhizobacteria interactions. The goal of this work is to encapsulate signal molecules, namely citric acid and naringin, an organic acid and a flavonoid, respectively, by a biodegradable polymer, polycaprolactone (PCL), in order to maintain the stability and activity of those signal molecules and enable their slow or controlled release over a selected period of time, according to the needs of the plants. This approach is expected to potentiate food crops, namely peanut crop, in adverse environmental conditions (water deficit), by promoting the beneficial interaction between the peanut plant (A. hypogaea) and rhizobacteria. The microcapsules (MCs) are obtained by an emulsion process combined with solvent evaporation technique and are characterized by scanning electron microscopy, thermogravimetry and Fourier transformed infrared spectroscopy. The kinetics of in vitro release of encapsulated molecules, in a period where the uptake of the compound in plants can occur, is studied. The encapsulation synthesis parameters that lead to the best